Trickster defeats the revolution: Egypt as the vanguard of the new authoritarianism - Armbrust, W (Routledge, 2017)
Egypt’s January 25th Revolution has often been implicitly viewed as a contest between the Mubarak regime and its cronies, who were able to prevail by pulling the levers of a “deep state,” and revolutionaries espousing progressive visions, albeit visions divided between those of Islamists and non-Islamists, and often seen by each as mutually incompatible with the other. The defeat of the January 25th Revolution’s progressive aspirations was to be understood, to a substantial degree, as a victory by the old regime. However, revolution understood as a Liminal Crisis allows us to see the rise of ‘Abd al-Fattah al-Sisi not as a straightforward restoration of the old regime, but as both a revolutionary outcome, and as an instantiation of a New Authoritarianism that has been making significant strides toward power in the wake of the revolutions that began in 2011. Liminality is understood here as the intermediate stage in a transition as described in Victor Turner’s Ritual Process, recently reinterpreted in the context of politics by Bjørn Thomassen. The potential dangers of liminality are often controlled by ritual, but this is not the case in revolutions, which become liminal crises precisely because there is no conventionalized means for closing off the state of being inbetween. In such circumstances Tricksters—beings at home in liminality often elaborated in myth, folklore, and literature—become potentially dangerous in politics. Sisi can be seen as a Trickster politician. But more broadly, the structuring of liminality through the global political-economic order of contemporary capitalism both creates a generalized precarity outside the most elite levels of society, and at the same time predisposes those compelled to live in precarity to be attentive to political Tricksters. Hence liminality can be seen as both the beginning and the end of revolution.